RAGE is a critical factor of sex-based differences in age-induced kidney damage - Bajwa, Seerat; Luebbe, Alexander; Vo, Ngoc Dong Nhi; Piskor, Eva-Maria; Kosan, Christian; Wolf, Gunter; Loeffler, Ivonne (Frontiers in Physiology, 2023)
Introduction: Advanced glycation end products (AGEs) are a heterogeneous group of molecules with potential pathophysiological effects on the kidneys. Fibrosis together with the accumulation of AGEs has been investigated for its contribution to age-related decline in renal function. AGEs mediate their effects in large parts through their interactions with the receptor for AGEs (RAGE). RAGE is a transmembrane protein that belongs to the immunoglobulin superfamily and has the ability to interact with multiple pro-inflammatory/pro-oxidative ligands. The role of RAGE in aging kidneys has not been fully characterized, especially for sex-based differences. Methods: Therefore, we analyzed constitutive RAGE knockout (KO) mice in an age- and sex-dependent manner. Paraffin-embedded kidney sections were used for histological analysis and protein expression of fibrosis and damage markers. RNA expression analysis from the kidney cortex was done by qPCR for AGE receptors, kidney damage, and early inflammation/fibrosis factors. FACS analysis was used for immune cell profiling of the kidneys. Results: Histological analysis revealed enhanced infiltration of immune cells (positive for B220) in aged (>70 weeks old) KO mice in both sexes. FACS analysis revealed a similar pattern of enhanced B-1a cells in aged KO mice. There was an age-based increase in pro-fibrotic and pro-inflammatory markers (IL-6, TNF, TGF-β1, and SNAIL1) in KO male mice that presumably contributed to renal fibrosis and renal damage (glomerular and tubular). In fact, in KO mice, there was an age-dependent increase in renal damage (assessed by NGAL and KIM1) that was accompanied by increased fibrosis (assessed by CTGF). This effect was more pronounced in male KO mice than in the female KO mice. In contrast to the KO animals, no significant increase in damage markers was detectable in wild-type animals at the age examined (>70 weeks old). Moreover, there is an age-based increase in AGEs and scavenger receptor MSR-A2 in the kidneys. Discussion: Our data suggest that the loss of the clearance receptor RAGE in male animals further accelerates age-dependent renal damage; this could be in part due to an increase in AGEs load during aging and the absence of protective female hormones. By contrast, in females, RAGE expression seems to play only a minor role when compared to tissue pathology.